An Analysis Of The Representastation Of Identity Theory And Struggle In The Film 8 Mile - Maria Matildis Lepan Ruron Ruron; Putu Suparna; Nuning Indah Pertiwi; Ni Putu Intan Pertamasari (Pasundan Social Science Development, 2026)
Film, as a form of mass media communication, possesses a powerful visual capacity to influence public opinion. It has a significant impact on audiences regarding various aspects of life, including perceptions of identity and struggle. The themes of identity and struggle as internal drives have influenced the film industry to portray characters who strive to discover their true selves through adversity. This study aims to analyze the representation of identity and struggle theories within the film 8 Mile. Data collection techniques employed include observation, interviews, and document analysis. This is a qualitative descriptive study utilizing a qualitative approach; specifically, it applies Tajfel and Turner’s social identity theory to analyze denotative and connotative meanings, scene descriptions, dialogue, lyrics, and relevant signs. The researcher analyzes specific scenes that embody social identity and struggle. Triangulation of sources and techniques is used, with validation achieved through informant interviews. The findings indicate that the organizational concept in 8 Mile is shaped by rules, role allocation, and communication patterns governing interactions among members of the rap community. Scenes in the film represent the pinnacle of the struggle for identity through rap battles, which serve as a space for social comparison. The study identifies three types of racism: sociocultural, biological, and economic. Future researchers are encouraged to expand upon the study of social identity using diverse subjects, such as films or television series. This research serves as an academic reference for developing communication studies regarding social identity and aims to raise awareness about the importance of respecting differences in social identity whether based on race, ethnicity, social status, or life background.